2010
DOI: 10.1590/s1984-46702010000300022
|View full text |Cite
|
Sign up to set email alerts
|

The role of seed mass on the caching decision by agoutis, Dasyprocta leporina (Rodentia: Agoutidae)

Abstract: ABSTRACT. It has been shown that the local extinction of large-bodied frugivores may cause cascading consequences for plant recruitment and overall plant diversity. However, to what extent the resilient mammals can compensate the role of seed dispersal in defaunated sites is poorly understood. Caviomorph rodents, especially Dasyprocta spp., are usually resilient frugivores in hunted forests and their seed caching behavior may be important for many plant species which lack primary dispersers. We compared the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
36
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 20 publications
3
36
0
4
Order By: Relevance
“…Here, we found that as fruit size increased, so did the probability of it being harvested and hoarded. Similar results have been reported for fleshy-fruited species in the Atlantic forest of Brazil [18,19], for Carapa procera in French Guiana [10] and for rodent-dispersed Fagaceae in Southwest China [17] Rodent preferences for large fruits or seeds have been interpreted in terms of the optimal foraging theory because larger fruits and seeds offer higher nutritional rewards per foraging bout [20,21,50], thus they are more appealing to be consumed or stored as food [3,4,15] and water reserves [29]. Furthermore, given that M .…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Here, we found that as fruit size increased, so did the probability of it being harvested and hoarded. Similar results have been reported for fleshy-fruited species in the Atlantic forest of Brazil [18,19], for Carapa procera in French Guiana [10] and for rodent-dispersed Fagaceae in Southwest China [17] Rodent preferences for large fruits or seeds have been interpreted in terms of the optimal foraging theory because larger fruits and seeds offer higher nutritional rewards per foraging bout [20,21,50], thus they are more appealing to be consumed or stored as food [3,4,15] and water reserves [29]. Furthermore, given that M .…”
Section: Discussionsupporting
confidence: 89%
“…Size is one of the most important fruit and seed traits, and its relationship with rodent foraging behavior has been extensively studied [1,4,11,12,17,18] because the decision to manipulate a fruit and/or seed is one of the most important from both the rodent and plant perspectives; moreover, its effects cascade down the successive steps in the foraging and scatter-hoarding process, and ultimately can influence seed dispersal dynamics [13]. Here, we found that as fruit size increased, so did the probability of it being harvested and hoarded.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the importance of secondary dispersal by scatter-hoarding rodents, the degree to which rodents are effective seed dispersers has rarely been measured due to methodological limitations (Galvez et al 2009;Galetti et al 2010). Most published studies of seed dispersal focus on the initial dispersal of seeds from the source plant and do not record additional (aka secondary) dispersal (Vander Wall et al 2005, Emmerson et al 2010.…”
Section: Introductionmentioning
confidence: 99%
“…Otra posibilidad es que las semillas no sean enterradas por ser muy pequeñas, ya que las semillas de masa menor a 0.9 g (i.e. Euterpe edulis) no serían enterradas por Dasyprocta (Galetti et al 2010); sin embargo, esto no aplica a las semillas de Mauritia, que tienen masas mucho mayores. También se ha observado ACTA AMAZONICA que Dasyprocta prefiere las semillas depredadas por brúquidos sobre aquellas que no lo están (Silvius y Fragoso 2002), debido posiblemente a que los endocarpios con brúquidos son más fáciles de abrir y que las larvas serían una buena fuente de proteínas y lípidos (Fragoso 1997;Silvius y Fragoso 2002).…”
Section: Discussionunclassified